Implementasi Sistem Informasi Monitoring Pengolahan Data Inventory Gudang Pada PT.Talaga Mulya Indah - Nurlaila Suci Rahayu Rais; Dedeh Apriyani; Gito Gardjito (UNIVERSITAS RAHARJA, 2020)
Monitoring of warehouse inventory data processing is an important thing for companies. PT Talaga mulya indah is still manual using paper media, causing problems that have an effect on existing information, namely: problems with data processing of incoming and outgoing goods. And the difference between data on the amount of stock of goods available with physical data, often occurs inputting data more than once for the same item, searching for available data, and making reports so that it impedes companies in monitoring inventory of existing stock of goods. Which aims to create a system that can provide updated information to facilitate the warehouse admin in making inventory reports, and reduce errors in input by means of integrated control. In this study, the authors used the data collection method used in this analysis using the method of observation, interviews, and literature review (literature study). For analysis using the PIECES analysis method. Furthermore, the system design used is UML (Unified Modeling Language). The results of this study are expected to produce the right data in the process of monitoring inventory data processing, also can provide the right information and make it easier to control the overall availability of goods.